THE INFLUENCE OF WORK CULTURE AND WORK ENVIRONMENT ON THE PERFORMANCE OF BEKANGDAM XIV/HASANUDDIN PERSONNEL - Ibrahim Ibrahim; Taufik Thahir; Mariati Mariati; Iqbal AR; Haeruddin Haeruddin (SEAN Institute, 2023)
This study aims to determine and analyze; 1) The influence of work culture and work environment on personnel performance in XIV Hasanuddin Transportation Supply (Bekangdam), 2) The influence of the work environment on Transportation Supplies (Bekangdam) XIV Hasanuddin. The research design used quantitative descriptive method using a population of 292 personnel and the sample used was Slovin's method with a sample size of 169 personnel. Descriptive analysis using the frequency distribution of the respondent's profile and the frequency of respondents' responses. While the data analysis used multiple linear regression method using SPSS 22 equipment with multiple linear regression analysis method using hypothesis test with F test, determinant test and t test. The results of the research obtained after testing the hypothesis, namely 1) work culture has a significant effect on the performance of personnel at the XIV Hasanuddin Transportation Supply (Bekangdam), 2) the work environment has a significant effect on the performance of personnel in XIV Hasanuddin Transportation Supplies (Bekangdam). The results of the study using the F test are that work culture and work environment simultaneously influence the performance of personnel at the XIV Hasanuddin Transportation Supply (Bekangdam) and have a very strong influence with R2 = 74.2% and the remaining 26.8% is influenced by other factors outside the study.